Assessing knowledge, attitudes, and practices toward sexually transmitted infections among Baghdad undergraduate students for research-guided sexual health education - Al-Gburi, Ghaith; Al-Shakarchi, Ali; Al-Dabagh, Jaafar D.; Lami, Faris (Frontiers in Public Health, 2023)
Background Sexually transmitted infections are common and tend to cause a lot of public misconceptions. This study was conducted to identify knowledge gaps and negative attitudes toward sexually transmitted infections and infected individuals among undergraduate students and give recommendations accordingly for the development of more objective research-guided health campaigns and school sex education programs. Method A cross-sectional study was conducted between May 17, 2022 and June 2, 2022 using a self-administrated questionnaire containing 84 items related to sexually transmitted infections distributed online to Baghdad-based university students. Result The sample consisted of 823 respondents; 332 men and 491 women. Overall knowledge was moderate to high, with 628 individuals (76.3%) answering more than half the questions correctly. There was no difference according to gender or previous sexual experience, but knowledge increased by an average of 2.73 points (p < 0.001) when a participant knew a previously infected individual. Less than half identified systemic symptoms of STIs, and their knowledge of other HIV items was also poor. Most respondents (85.5%) agreed to the need for sex education during middle or high school and cited traditional barriers as the most critical barrier (64.8%); in comparison, those who did not agree on its need cited the sensitivity of the subject (40.3%) or religious barriers (20.2%) as more important. Conclusion Specific knowledge gaps exist for HIV and non-HIV sexually transmitted infections; these should be addressed during sex education, focusing on specific high-risk groups. Negative attitudes and stigmatizing behavior should be addressed as well by increasing focused STI knowledge.